Professional Self-Determination and Professional Identity of Students-Teachers in the Conditions of Individualisation of Education - E. G. Belyakova; I. G. Zakharova (Образование и наука)
Introduction. In the context of increasing transfessionalism of labour market and growing socio-economic uncertainty, modern students, including future teachers, should not only master the chosen specialty, but also be ready for meaningful entry into the profession. This process, which does not work according to the traditional model, but implements the principles of individualisation of education, has not been studied yet in higher education. The lack of analytical information on professional self-determination implementation, what affects it and students’ perceptions of their own professionalism do not allow psychological and pedagogical preparation for the upcoming employment to be purposefully and effectively organised.Aim. The present research is aimed at identifying the general and specific characteristics of professional self-determination of students-teachers of primary courses of undergraduate studies, while their training is organised through individual educational trajectories.Methodology and research methods. The development of the research procedure was based on the provisions of the author’s concept of semantic mechanisms of professional self-determination, according to which the basic types of activity of the subject of the professional path are the design of the professional future, its active implementation and reflective understanding of experience. The diagnostic complex combined the assessment of students' professional self-determination through objective methods with the opinions of students themselves about the process of their professional development. Processing of the results included descriptive statistics procedures and data clustering using the K-means method.Results and scientific novelty. Typological groups of students are identified taking into account different indicators of professional self-determination and professional identity. It has been established that there are at least four different variants of professional self-determination in the junior years of Bachelor’s programmes in Pedagogy (“positive pedagogical identity”, “teachers making choice”, “undecided” and “non-educators”). Detailed differences between these groups are presented. The parameters of differences include the formation of a personal professional plan, an emotional attitude to the profession, degrees of conscious activity, self-esteem “I am a professional”, subjective satisfaction with professional deve lopment based on the following interconnected aspects: accepted values of teaching profession, self-efficacy in solving pedagogical problems, opportunities for self-realisation and for choosing a direction and development methods, experiencing identity, understanding of own vocation, motivation for pedagogical activity. It is noted that positive respondents’ self-identification in the teaching profession is combined with high activity in the development of pedagogical experience from various sources. It is concluded that there is the need for differentiated psychopedagogical support of students taking into account the characteristics of their professional self-determination.Practical significance. The model, previously designed by the authors to accompany professional self-determination of teachers-students, is clarified. In accordance with the results obtained, the authors make recommendations concerning the development of content and organisation of such support in the conditions of educational process individualisation.